Pengaruh Disiplin Kerja dan Lingkungan Kerja Fisik terhadap Kinerja Karyawan pada Kantor Akuntan Publik Jamaludin, Ardi, Sukimto & Rekan Jakarta Pusat - Muhamad Hafizh Dzakwan; Suwanto, Suwanto (Yayasan Literasi Sains Indonesia, 2024)
The purpose of this study was to determine Work Discipline, and Physical Work Environment on employee performance at the Jamaludin, Ardi, Sukimto & Rekan Public Accounting Firm, Central Jakarta. The method used is quantitative. Sampling technique used is saturated with a sample of 50 respondents, the test used is validity test, reliability test, classical assumption test, linear regression test, determination coefficient test, hypothesis test (t test and f test). The results of this study simultaneously have a significant effect on employee performance with regression Y = 1.672 + 0.622 X1 + 0.342 X2 , the correlation coefficient value of 0.861 means that simultaneously has a very strong level of relationship where the value is in the interval 0.80 - 1000. While the coefficient of determination (R Square) is 0.741 (74.1%). Based on this value, it shows that the percentage between the work discipline variable (X1), and the physical work environment (X2) affects employee performance (Y) by 74.1% while the rest (100%-74.1%) = 25.9% is influenced by other variables that are not included. For the hypothesis value, the value of Fcount> Ftabel or (10,357> 2,011). This is also reinforced by sig <0.05 or (0.000 <0.05) thus Ho is rejected and Ha is accepted, this shows that there is a simultaneous significant influence between the variables of Work Discipline (X1) and Physical Work Environment (X2) on Employee Performance (Y) at the Public Accounting Firm Jamaludin, Ardi, Sukimto & Partners Central Jakarta.